ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAN MANUFAKTUR YANG TERDAFTAR DI BEI - DINA ARIESTA (Universitas Katolik Widya Mandala Surabaya, 2012)
Corporate managers has more awareness of internal information and corporate prospects in the future than the investor. Therefore, managers is obliged to disclose finance information in order to know the financial performance of the company which can be used to measure profit. Corporate profits come for managers who can run the company effectively and efficiently. Therefore, this study aims to examine the influence of organizational culture, managerial and funding to the company's profitability. Study sample was 30 manufacturing companies listed on the Indonesia Stock Exchange in the period 2007-2009. This study was a quantitative research design with hypotheses and data sources obtained from the website of the Indonesia Stock Exchange (www.idx.co.id). The technique used is multiple linear regression analysis.The analysis showed that the organizational, managerial, culture and financing have positive effect on corporate profitability. Organizational culture is important and can deal with problems and opportunities of internal and external environment. The bigger the profit the company's total assets (wealth) which belongs to the company. More generated by a company means that profits the assets are hight become.